Genetic effects of circulating hormone and proteome on amyotrophic lateral sclerosis identified by Mendelian randomization - Xinyue Fan; Yinting Zeng; Feifei Zhang; Yang Xu; Qixuan Duan; Shuting Long; Yumeng Lin; Kai Wang; Li Jiang (Scientific Reports)
Abstract Altered circulating hormones in ALS patients have been widely reported by previous observational studies, but whether these relationships are causal is unclear. Moreover, the potential therapeutic targets for ALS and the effects of plasma protein fluctuation on ALS progression are not fully understood. Therefore, we conducted a Mendelian randomization (MR) study to evaluate the causal role of 5 hormonal risk factors (insulin-like growth factor-1, IGF-1; sex hormone-binding globulin, SHBG; free testosterone, FT; total testosterone, TT; and estradiol) in ALS risk. Furthermore, we screened up to 90 circulating proteins including cytokines, chemokines, growth factors, and interferons, to identify potential therapeutic targets for ALS. Our MR analysis found genetically predicted higher level of FT was associated with a 23% lowered risk of ALS. Further screening of proteomic traits found that 12 plasma proteins were causally associated with ALS. These findings suggest that higher FT potentially exerts a protective effect on ALS risk. Several proteins may act as potential circulating biomarkers and therapeutic targets for ALS. In the future, high-throughput proteomic analyses and experimental explorations are likely needed to clarify the regulated role and mechanistic pathways.